2017
DOI: 10.1128/genomea.00842-17
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Citrobacter freundii 705SK3, an OXA-48-Encoding Wastewater Isolate

Abstract: We present the genome sequence of Citrobacter freundii 705SK3, a wastewater isolate harboring an IncL OXA-48-encoding plasmid. Assembly of the genome resulted in a 5,242,839-bp circular chromosome (GC content, 52%) and two closed plasmids of 296,175 bp and 63, 458 bp in size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Linear genomic comparisons revealed that a conserved backbone, including the two unclassified replicons repA and repB, were identified between pS39-1 and another two untypable fosA3-bearing plasmids pTEM-2262 and pMH17-012N_4 in C. freundii isolates of pig and human origin from China Zhang et al, 2019; Figure 2). Noticeably, pTEM-2262 also shared a conserved backbone with another four untypable non-fosA3bearing plasmids from different species including C. freundii, Kosakonia radicincitans, and Citrobacter werkmanii with origins including the environment, vegetables and humans (Zhou et al, 2017;Zurfluh et al, 2017;Becker et al, 2018;Barry et al, 2019). These indicated that the untypable and conjugal p12-1-like and pS39-1-like plasmids could act as vectors for fosA3 transmission between different Enterobacteriaceae from different ecological niches.…”
Section: Discussionmentioning
confidence: 95%
“…Linear genomic comparisons revealed that a conserved backbone, including the two unclassified replicons repA and repB, were identified between pS39-1 and another two untypable fosA3-bearing plasmids pTEM-2262 and pMH17-012N_4 in C. freundii isolates of pig and human origin from China Zhang et al, 2019; Figure 2). Noticeably, pTEM-2262 also shared a conserved backbone with another four untypable non-fosA3bearing plasmids from different species including C. freundii, Kosakonia radicincitans, and Citrobacter werkmanii with origins including the environment, vegetables and humans (Zhou et al, 2017;Zurfluh et al, 2017;Becker et al, 2018;Barry et al, 2019). These indicated that the untypable and conjugal p12-1-like and pS39-1-like plasmids could act as vectors for fosA3 transmission between different Enterobacteriaceae from different ecological niches.…”
Section: Discussionmentioning
confidence: 95%
“…For the study, the clinical isolate C. freundii CF8 applied in the present study demonstrated a high resistance to antibiotics and was a robust biofilm producer. It is known that multi-resistant and strongly biofilm forming strains have virulence factors, probably contributing to the strain pathogenicity and to the difficulty in treating the disease in fish (Zurfluh et al, 2017). Accordingly, precaution measures are required to manage infections by C. freundii strain.…”
Section: Discussionmentioning
confidence: 99%
“…C. freundii belongs to a normal flora of the fish and human intestine, as well as a conditionally pathogenic bacteria capable of infecting people that exhibit low immunity, which will cause several diseases (e.g., pneumonia, meningitis, sepsis, bacteremia, and urinary tract infections) (Anderson et al, 2018;Ando et al, 2018;Liu et al, 2018). Furthermore, C. freundii has been associated with numerous diseases and symptoms (e.g., hemorrhagic septicemia, severe enteritis and serious lesions in kidney and gills of catfish; systemic infection in common carp; tail necrosis, septicemia, hemorrhage, as well as reddening of the body in Mozambique tilapia; high mortality in Nile tilapia; cutaneous hemorrhages in zebrafish; tail necrosis, septicemia, hemorrhage as well as reddening of the body in Mozambique tilapia; high mortality in Nile tilapia; gastroenteritis and progressive high-mortality in rainbow trout; systemic infection in common carp) (Zurfluh et al, 2017;Castanheira et al, 2018;Hassen et al, 2020). C. freundii has been reported to resist numerous commonly used antibiotics since its discovery.…”
Section: Introductionmentioning
confidence: 99%
“…Members of the genus Citrobacter belong to the family Enterobacteriaceae, which are ubiquitous in diverse habitats such as wastewater, sludge, sediment, and soil [1][2][3][4][5]. They are opportunistic human pathogens that have been wellstudied for their pathogenicity and multidrug resistance traits [6].…”
Section: Introductionmentioning
confidence: 99%